RELEVANSI ANTARA HADITS DAN SAINS Kaedah dan aplikasinya Dalam Bingkai I`jaz Ilmi - Helmi Basri (AL-FIKRA, 2018)
Analyzing a substance of hadits is the most crucial point in the way of interacts with hadits itself. We will be more understood about the content of hadits by using this way, not only written but also implicit. A part should be analyzed is a balance of what prophet Muhammad SAW say is with scientific fact nowadays. It make us admit that most of research now are related to hadits or sunnah Rasulullah SAW. Therefore, the relevance of hadits and science is called by I`Jaz Ilmi. I’jaz Ilmi in hadits can be seen in several parts, such as in health problem, medical science and other science. Say for example in health problem, there are many suggestions of our prophet that are related to medical science. Furthermore, analyzing hadits I`jazul Ilmi in part of I’jazul Hadist must be done by special people who have competence in this field, and based on the rules to give legitimation in that analyses. Using Hadist as a guidance is a must, because the first function of hadits is become a guidance in human life, without thinking about the relevance of hadits and science.